Role for intracellular platelet-activating factor in the circulatory failure in a model of gram-positive shock. - De Kimpe, S. J. (1995)
1. This study investigates the effects of two structurally different antagonists of platelet-activating factor (PAF), BN52021 and WEB2086, on the circulatory and renal failure elicited by lipoteichoic acid (LTA) from Staphylococcus aureus (an organism without endotoxin) in anaesthetized rats. 2. Administration of LTA (10 mg kg-1, i.v.) caused hypotension and vascular hyporeactivity to noradrenaline (1 microgram kg-1, i.v.) WEB2086 (5 mg kg-1, i.v., 20 min before and 150 min after LTA) inhibited the delayed fall in mean arterial blood pressure (at 300 min: 99 +/- 6 mmHg vs. 75 +/- 6 mmHg, P < 0.01) and prevented the decrease in pressor response to noradrenaline (at 300 min: 36 +/- 5 mmHg min vs. 17 +/- 5 mmHg min, P < 0.01). Surprisingly, BN52021 (20 mg kg-1, i.v., 20 min before and 150 min after LTA) neither prevented the hypotension (74 +/- 6 mmHg) nor the vascular hyporeactivity (21 +/- 5 mmHg min). However, BN52021 inhibited the hypotension to injections of PAF as well as the circulatory failure elicited by lipopolysaccharides (10 mg kg-1, i.v.). 3. LTA caused an increase in plasma concentration of creatinine from 39 +/- 5 microM (sham-operated) to 70 +/- 8 microM and urea from 4.7 +/- 0.1 to 13.1 +/- 1.6 mM. The renal failure elicited by LTA was significantly inhibited by WEB2086 (creatinine: 45 +/- 4 microM and urea: 5.7 +/- 0.7 mM), but not by BN52021. 4. The induction of nitric oxide synthase activity in lungs by LTA was attenuated by WEB2086 from 98 +/- 17 to 40 +/- 15 pmol L-citrulline 30 min-1 mg-1 protein (P < 0.01), but not by BN52021 (148 +/- 21 pmol L-citrulline 30 min-1 mg-1 protein). Similarly, WEB2086, but not BN52021, inhibited the increase in plasma nitrite concentration associated with the delayed circulatory failure caused by LTA. The release of tumour necrosis factor-alpha (TNF-alpha) after injection of LTA was not attenuated by WEB2086. 5. The induction of nitrite release by cultured macrophages activated with LTA (10 micrograms ml-1 for 24 h) was inhibited by 74 +/- 4% by WEB2086 (3 x 10(-4) M), but not by BN52021, indicating that only WEB2086 acts on intracellular PAF receptors. 6. Thus, the intracellular release of PAF contributes to the circulatory and renal failure and induction of nitric oxide synthase elicited by LTA in anaesthetized rats. The difference between the two structurally different PAF antagonists in our septic shock models using either LTA or lipopolysaccharide (LPS), shows the importance of models for Gram-positive sepsis in the elucidation of the pathophysiology of septic shock and for the evaluation of potential drugs.